Fabrication and characterization of green synthesized ZnO nanoparticle based dye-sensitized solar cells - Shashanka, R. (H. : ĐHQGHN, 2020)
In the present study, we report on the synthesis of ZnO nanoparticles using Tilia Tomentosa (Ihlamur) leaves extract followed by calcination at 400 C for 15 min. The prepared ZnO nanoparticles were characterized by XRD and SEM to study the phase and microstructure, respectively. The XRD analysis showed the absence of impurity peaks and the SEM image confirmed the spherical nature of the prepared ZnO nanoparticles with an average particle size of 80 nm. UV-Visible spectroscopy was used to study the optical properties, and the bandgap was calculated to be 3.55 eV. This large bandgap is attributed to the property of the semiconductor, which can be explored for solar cell applications. Therefore, we used green synthesized ZnO nanoparticles to fabricate dye-sensitized solar cells (DSSC). From the J-V curves, we calculated the DSSC parameters such as open-circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF) and efficiency (h), and their values were 0.65 V, 6.26 mA, 48.5%, and 1.97%, respectively, at 100 mW/cm2.